2011
DOI: 10.1007/s10286-011-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

Severity of autonomic dysfunction in patients with complete spinal cord injury

Abstract: A complete loss of supraspinal control was observed in all, with a reflex isolated spinal cord in all but one patient. We confirm that in most SCI subjects there is concordance between the impairment of sympathetic function and somatic impairment. To assess autonomic dysfunction, a battery of tests should include SSR, abdominal electrical stimulation and Valsalva maneuver, as they combine pressor stimuli above and below the lesion and assess both cholinergic and sudomotor pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…Presumably, complete sensorimotor lesions (AIS A) above T1 would result in absent or abnormal palmar SSRs, as the palmar SSR is thought to originate at the T1-T3 levels. 10,25,47 Similarly, plantar SSRs would be absent in complete neurological injury above T10, with plantar SSRs generated between T10-L2. 10,25,47 Correspondingly, in those patients with complete neurological lesions below these levels, it would be expected to see preserved responses.…”
Section: Completeness and Localization Of The Autonomic Lesionmentioning
confidence: 95%
See 3 more Smart Citations
“…Presumably, complete sensorimotor lesions (AIS A) above T1 would result in absent or abnormal palmar SSRs, as the palmar SSR is thought to originate at the T1-T3 levels. 10,25,47 Similarly, plantar SSRs would be absent in complete neurological injury above T10, with plantar SSRs generated between T10-L2. 10,25,47 Correspondingly, in those patients with complete neurological lesions below these levels, it would be expected to see preserved responses.…”
Section: Completeness and Localization Of The Autonomic Lesionmentioning
confidence: 95%
“…Previnaire et al 10 suggested that in order to fully characterize autonomic dysfunction in SCI, a battery of autonomic tests including SSRs, blood pressure response to Valsalva maneuver and response to perturbation below the lesion (i.e. with abdominal electrical stimulation) should be performed.…”
Section: Completeness and Localization Of The Autonomic Lesionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any signal, the spectrum may cover wide range of frequencies and conventional time and frequency domain analysis techniques based on the linear fluctuation of heart rate is insufficient to outline the changes in heart rate dynamics [25][26][27][28][29][30][31][32][33][34][35][36]. To quantify this, nonlinear dynamics based methods such as fractal analysis and chaos theory have been introduced [37][38][39]. These techniques have quite successfully been implemented on HR signals and provided significant clinical information on cardiac diseases [40][41][42][43][44][45], but are yet to be used on a few more fields like evaluation of autonomic cardiovascular dysfunction in epilepsy etc.…”
Section: Translational Biomedicine Issn 2172-0479mentioning
confidence: 99%